Renewable-Based Microgrids: Design, Control and Optimization - Tostado-Véliz, Marcos; Arévalo, Paul; Kamel, Salah; El-Sehiemy, Ragab A.; Senjyu, Tomonobu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue aimed to collate recent works regarding the planning and control of energy systems. In particular, this Special Issue focuses on microgrids. This kind of system enables optimal integration of renewable energy sources, electric vehicles, energy storage, and demand-side management strategies, thus proposing a valuable framework through which to implement the decarbonization of the electricity sector. Special attention is given to those works devoted to systems with high penetration of renewables and advanced demand response strategies. Literature reviews are also included in this Special Issue, and some real-life experiences are described and analyzed.